Urinary Extracellular Vesicles as Source of Biomarkers in Kidney Diseases - Gámez-Valero, Ana; Lozano-Ramos, Sara Inés; Bancu, Ioana; Lauzurica-Valdemoros, Ricardo; Borràs, Francesc E. (Frontiers in Immunology, 2015)
Most cells physiologically release vesicles as way of intercellular communication. The so-called Extracellular Vesicles (EVs) include exosomes, ectosomes and apoptotic bodies, which basically differ in their composition and subcellular origin. Specifically, EVs found in urine reflect the state of the urinary system, from podocytes to renal tubular cells, thus making them an excellent source of samples for the study of kidney physiology and pathology. Several groups have focused on defining biomarkers of kidney-related disorders, from graft rejection to metabolic syndromes. So far, the lack of a standard protocol for EVs isolation precludes the possibility of a proper comparison among the different biomarkers proposed in the literature, stressing the need for validation of these biomarkers not only in larger cohorts of patients but also considering the different methods for EVs isolation. In this review, we aim to gather the current knowledge about EVs-related biomarkers in kidney diseases, with a special emphasis in the methods used to date for EVs enrichment, and discussing the need for more specific protocols of EV isolation in clinical practice.